Journal editor assistance: Copyediting and OJS management at Universitas Nahdlatul Ulama Indonesia - Vika Nurul Mufidah; Nadiah Nurli Fadilah; Fariz Alnizar; Dwi Winarno (Community Empowerment, 2022)
The lack of knowledge related to OJS management and the job desk of journal managers made LPPM Unusia organize workshops for journal editors: editing and managing OJS. The activity uses a mentoring method consisting of three stages, namely pre-activity, core activity and post-activity. The results of the assistance revealed that there was an increase in knowledge of journal managers regarding job desks and OJS management.